PENYELIDIKAN WEAK ZONE MENGGUNAKAN METODE WELL LOGGING DIKECAMATAN MONTASIK DAN INGIN JAYA, ACEH BESAR - AMSIR AMSIR; ZAKIA MASRURAH; NURUL AZMI; MUHAMMAD SYUKRI; CUT ZAHARA ROZA (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2023)
Weak zone investigation using well logging method in Montasik and Ingin Jaya sub-districts, Aceh Besar has been conducted at ten borehole points. In this study, the well logging method was used to obtain and determine the presence of weak zones in ten boreholes in Aceh Besar District. The subsurface data obtained from this well logging method is in the form of cutting data, namely subsurface rock lithology and electrical logging data, namely resistivity log values. Based on the results of data analysis and interpretation, these ten boreholes have weak zones and the most significant ones are found at four borehole points, namely boreholes T1, T2, T5, and T10. Point T1 is located at a depth of 76 - 106 m, which is a clay layer with a resistivity value of 105 - 289 Ωm. Point T2 is at a depth of 45 - 57 m, which is a sand layer with a resistivity value of 32 - 38 Ωm. Point T5 is at a depth of 0 - 40 m, which is a clay layer with a resistivity value of 26 - 184 Ωm. Point T10 is at a depth of 60 - 62.5 m and 62.5 - 80 m, namely there are layers of sand and passive clay with resistivity values of 3 - 117 Ωm and 3 - 111 Ωm. keywords: Aceh Besar, resistivity value, Well Logging, Weak Zone